Survival techniques making fires, finding water, building shelters, hunting, navigation, natural disasters, first aid - Stilwell, Alexander (AMBER Books LTD, 2011)
Survival Techniques takes you through all the things you need to know about surviving disasters and staying alive in the wild, such as where to find water in the desert; how to build shelters from locally available materials; what plants are safe to eat and what are deadly poisonous; and what animals will pose a threat in survival situations.